Load Dependence Behavior Of The Thermoelectric Module Energy Harvesting System By Inverse Dynamic Analysis–Maximum Power Point Tracking - R. Mohamed, R. Mohamed; A. Mohamed, A. Mohamed; Md Yusop, Azdiana; Sulaiman, Noor Asyikin (Science Publishing Corporation, 2019)
This paper presents the characterization behavior of a thermoelectric module (TEM) analysis by the implementation of a new inverse dynamic analysis–maximum power point tracking (IDA-MPPT), with different load resistance values to the common maximum power point circuit (MPPC) controller. In this study, a conventional TEM test unit measurement is performed consists of a hotplate and a TEM module. The two MPPC boards are fed with the harvested voltage from the TEM module and a supercapacitor is linked with it. The load resistor is then fed with the boosted voltage of the second board. The three phases experimental analysis is introduced in a closed loop manner. There are, TEM system analysis without the IDA-MPPT implementation, TEM system analysis with IDA-MPPT implementation, and a newly developed IDA-MPPT unit experimental analysis. Results have shown that the TEM system with IDA-MPPT implementation with 1kΩ resistor is capable of achieving 5V output stable line voltages with 83.33% efficiency. In conclusion, with the input stable voltage of the MPPC board from the new input –shaping process, a satisfactory load behavior is achievable by its voltage readings.